SCMTool: A Graphical Tool for Smart Contract Modeling - Velasco, Gislainy Crisostomo; Vieira, Dionatan Alves; Vieira, Marcos Alves; Carvalho, Sergio T. (Anais do Colóquio em Blockchain e Web Descentralizada (CBlockchain); 2023: Anais do I Colóquio em Blockchain e Web DescentralizadaDO - 10.5753/cblockchain.2023.230560, 2023)
The development of smart contracts in the Ethereum Virtual Machine (EVM) can be a complex task, both for experienced and beginner developers. Understanding these contracts can be challenging for both technical and non-technical users, due to the difficulty in comprehending the connection between the elements and resources available, as there is no clear way to visually present the functionalities of a contract and its relationships. In this paper, we introduce the Smart Contract Modeling Tool (SCMTool), a graphical tool based on the Model-Driven Engineering approach, that allows users to specify models that represent the structure of a smart contract in a simpler and more intuitive way. The tool was validated using a use case from the NFT industry.